2015 IEEE International Conference on Space Optical Systems and Applications (ICSOS) 2015
DOI: 10.1109/icsos.2015.7425074
|View full text |Cite
|
Sign up to set email alerts
|

Optical feeder links for high throughput satellites

Abstract: Optical feeders for geostationary High Throughput Satellites (HTS) systems based on 1.55µm wavelength technology are expected to enable to transmit up to several terabits over one active link. A desirable option of transmission architecture is an optical feeder link transparent with respect to the user air interface. This can be implemented using either a digital or an analog modulation of the optical carrier. The digital option increases the optical bandwidth to be transmitted, however it benefits from error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…The real differentiator may actually be the availability of optical ground terminals, which is expected to start from small dimension telescopes, so more favourable to a large N+P networks. Variants like clusters of small optical terminals discussed in [3] may be equally attractive.…”
Section: Cost Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The real differentiator may actually be the availability of optical ground terminals, which is expected to start from small dimension telescopes, so more favourable to a large N+P networks. Variants like clusters of small optical terminals discussed in [3] may be equally attractive.…”
Section: Cost Analysismentioning
confidence: 99%
“…While there is clear interest to use optical communications in VHTS feeder links ( [1], [2], [3]), thanks to their very large capacity, several challenges need to be resolved before they can be adopted by satellite operators. A companion paper in the same conference [4] investigates different options for the feeder link technologies and presents several solutions for the satellite payload.…”
Section: Introductionmentioning
confidence: 99%
“…Free space optical communications are seen as a key technology [11,13,16] to cope with the needs of high data rate payloads for future low-earth orbiting observation satellites in replacement or in addition to current radio-frequency technologies. While the latter are very mature and well proven technologies which have been used for decades, the former may be able to offer data rates beyond the reach of radio-frequency technologies.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…The resulting networks were then analyzed using orbital information from various existing low-earth orbiting satellites (identical to [7]). It was shown that mid-latitude stations could handle between 5 and 9 Tb of data per day, while high-latitude stations could not handle more than 16 Tb of data per day. While these results were less optimistic than the ones proposed in a previous paper [7], comparisons showed that even small networks of optical ground stations using low data rates (10.5 Gbps) could outperform radio-frequency throughputs.…”
mentioning
confidence: 99%
“…Free-Space-Optical (FSO) communications are seen as a key technology [6] [8] [11] to cope with the needs of higher data-rate payloads for future lowearth orbiting (LEO) observation satellites in replacement to the current radiofrequency (RF) technologies. Current RF technologies use X-Band for download which can currently provide up to a few Gbps [2].…”
Section: Introductionmentioning
confidence: 99%